Climate variability impact on water requirement of spring maize in central and sub-mountainous Punjab - Majumder, Debjyoti; Kingra, P.K.; Singh, Sompal (Annals of Agricultural Research, 2016)
Long-term variability in potential evapotranspiration (PET) of spring maize during the period 1985-2014 was assessed for two agroclimatic regions i.e. Ludhiana representing central plain region andBallowal Saunkhari representing sub-mountainous agroclimatic region of Punjab. PET of springmaize has been observed to increase over years at both the locations @ 1.3 mm year–1 at Ludhianaand 2.9 mm year–1 at Ballowal Saunkhari. During the period of three decades, Ludhiana experiencedlowest of 693.0 mm of PET during 1997 and highest 931.9 mm during 2010, while, Ballowal Saunkhariexperienced lowest PET of 723.7 mm during 1992 and a highest of 954.7 mm during 2010 during thegrowing period of spring maize. Day time temperature was found to have positive correlation withPET of spring maize at Ludhiana (r = 0.87) and Ballowal Saunkhari (r = 0.90). Similarly, morningand evening RH were negatively correlated with PET at Ludhiana (r = –0.56 and –0.42) and BallowalSaunkhari (r = –0.36 and –0.31). Multiple regression models explained 75 to 82 per cent variation inPET of spring maize at Ludhiana and 79 to 90 per cent variability at Ballowal Saunkhari because ofthe weather parameters. The study indicates that increase in water requirements under warmingscenarios will put more pressure on already depleting water resources in the state and hence needto be managed in view of changing climatic conditions.